Impeller radial velocity and air flow rate influence on copper rougher flotation recovery = Wpływ prędkości obrotowej wirników i stopnia napowietrzenia zawiesiny flotatycjnej na przebieg operacji flotacji głównej miedzi - Bazan, Bartosz; Potulska-Bazan, Aleksandra; Witecki, Kajetan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A rougher flotation study has been done to analyze the effects of copper feed mineralogy, air flow rate and impeller radial velocity on metallurgical performance. During the performance testing the trials were exposed to metallurgical examining and computerised mineral analysis to establish a size-by-size mineralogy.
Keywords: flotation; copper ores; liberation; flotacja; rudy miedzi; stopień uwolnienia